Radio resource management in MIMO-OFDM- mesh networks issues and approaches. - Niyato, Dusit; Hossain, Ekram
We present a survey on the radio resource management issues in MIMO-OFDM-based infrastructure wireless mesh networks. The major components in radio resource management (i.e., scheduling and admission control) and related research issues are discussed. We review related work in the literature. We propose a game-theoretic model for admission control in IEEE 802.11n-based WMNs using the MIMO-OFDM technology. The proposed scheme uses Q-learning, which is a reinforcement learning algorithm, to gain knowledge on system performance. Then this knowledge is used to determine payoff for the game formulation to obtain the Nash equilibrium for the decision on admitting or rejecting a new connection at a mesh router.
Keywords: IEEE 802.11n-based WMN; MIMO-OFDM-based wireless infrastructure mesh network; Nash equilibrium; Q-learning.; Admission control; Game-theoretic model; Mesh router; Radio resource management; Reinforcement learning algorithm